DAMPAK PERKULIAHAN LURING TERHADAP PENDAPATAN MASYARAKAT SEKITAR KAMPUS IAIN PEKALONGAN - Emilia Alfiesyah (Sahmiyya, 2022)
The impact of the COVID-19 pandemic has resulted in reduced labor supply, unemployment, reduced income, increased costs of doing business in every sector, reduced consumption due to shifts in consumer preferences for each item, people's vulnerability to disease and vulnerability to changes in economic conditions. The pandemic also has an impact on students because online learning and working from home for educators are changes that must be made by lecturers to continue teaching students. The type of research used is the library research method, where research is carried out by taking data through library research. By using literature study, researchers can explore the basic theories and concepts that have been found by previous researchers. Consumptive lifestyle among IAIN Pekalongan students as an effort to increase prestige in the campus environment. The occurrence of economic changes in students is caused by other IAIN Pekalongan students with higher economic levels, wider social imagery, more modern knowledge of technology and information, and several other causes. A business opportunity is an opportunity that an entrepreneur has to achieve his business goal, namely returns, by doing a business that utilizes the various resources he has. With the existence of the IAIN Pekalongan campus, the surrounding community has business opportunities to improve the economy by establishing several businesses. The existence of the IAIN Pekalongan campus in general has an impact on the community's new economic growth, which can be seen by the increasing number of new types of businesses being found. This increase in income for the community is expected to have an impact, especially in the form of changes in people's attitudes about life regarding the education of their children.